The Use of the Field Trip to Engage Students' Interest in Writing Descriptive Text - Fabella Ulfiantari; Rosnija, Eni; Supariati, Supariati (PANYONARA: Journal of English Education, 2023)
Students’ interest affects the quality of the learning process. This study aims to improve the quality of the learning process of writing descriptive text by applying the field trip method. This study was conducted in classroom action research, with 7 th- grade students of SMPN 11 Pontianak as its subject. The instruments used in this study included the observation checklist, field notes, interview, and writing test. At the same time, the data analysis is done through an interactive analysis technique. This study was done in two cycles, each consisting of planning, acting, observing, and reflecting activities. This study's result showed that implementing the field trip method in writing the descriptive text improved the students’ learning interest. This result indicated the percentage of students’ attention, willingness, activeness, participation, and happiness that increased during cycles I and II. In addition, it also improved the quality of students’ writing, on aspects word choice, coherence, and sentence structure. According to the quantitative data, the students' cycle 1 test score was 72.18, and their cycle II test score was 80.03. In conclusion, applying the field trip method in teaching writing descriptive texts has proven successful in improving students' interests and abilities.